A COMPARATIVE STUDY OF WORD ORDER OF KASHMIRI AND SHINA - Hassan, Sheeba; Hassan, Tahseen (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This paper compares the clause-level word order of two Dardic (Indo-Aryan) varieties spoken in India’s Gurez Valley: Kashmiri spoken in Kashmir and Gurezi Shina in Gurez Valley (UT) of Jammu and Kashmir. We report on fieldwork eliciting parallel sentences in each language, categorising them by syntactic (simple, compound, complex) and semantic types (negative, imperative, interrogative, declarative, exclamatory). Our findings show that Gurezi Shina maintains a rigid SOV structure in nearly all contexts. In contrast, Kashmiri exhibits a more flexible, verb-second (V2) pattern with surface SVO or OSV orders in main clauses (as noted by Bhatt). We highlight how Kashmiri’s underlying SOV order surfaces differently in subordinate clauses (consistent with Bhatt’s observations), while Gurezi Shina consistently places the finite verb clause-finally. These contrasts have implications for typology (rigid vs. flexible OV/VO alignment), linguistic history (Dardic vs. Indo-Aryan features), and processing (different subject placement strategies). Our results confirm that Gurezi Shina aligns with the common SOV typology of Himalayan languages, whereas Kashmiri remains an Indo-Aryan anomaly with Germanic-like V2 behaviour.